2012
DOI: 10.3390/polym4021025
|View full text |Cite
|
Sign up to set email alerts
|

Radical-Scavenging Activity of Thiols, Thiobarbituric Acid Derivatives and Phenolic Antioxidants Determined Using the Induction Period Method for Radical Polymerization of Methyl Methacrylate

Abstract: Abstract:The radical-scavenging activities of two thiols, eight (thio)barbituric acid derivatives and six chain-breaking phenolic antioxidants were investigated using the induction period method for polymerization of methyl methacrylate (MMA) initiated by thermal decomposition of 2,2'-azobisisobutyronitrile (AIBN) and monitored by differential scanning calorimetry (DSC). The induction period (IP) for the thiols 2-mercaptoethanol (ME) and 2-mercapto-1-methylimidazole (MMI) was about half that for phenolic antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Table 1 shows the average molecular weight (M w a ), number average molecular weight (M n a ), and polydispersity (PDI) for the respective oligomers. 32 Thermal stability of OCA and OCMA were evaluated by heating the sample at a rate of 10 1C min À1 under a nitrogen atmosphere. As shown in Table 1, the yield of oligomers OCMA1 and OCA1 was 74% and 65%, respectively, whereas the yield for OCMA2 and OCA2 was 40% each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the average molecular weight (M w a ), number average molecular weight (M n a ), and polydispersity (PDI) for the respective oligomers. 32 Thermal stability of OCA and OCMA were evaluated by heating the sample at a rate of 10 1C min À1 under a nitrogen atmosphere. As shown in Table 1, the yield of oligomers OCMA1 and OCA1 was 74% and 65%, respectively, whereas the yield for OCMA2 and OCA2 was 40% each.…”
Section: Resultsmentioning
confidence: 99%
“…As reported earlier, the antioxidant property inhibits the free radical polymerization. 32 Thermal stability of OCA and OCMA were evaluated by heating the sample at a rate of 10 1C min À1 under a nitrogen atmosphere. Both OCMA1 and OCMA2 underwent degradation at about 232 1C, although there was a slight difference in molecular weight.…”
Section: Resultsmentioning
confidence: 99%
“…NMR analysis indicated that more than 86% of the treated monomer still exhibited an intact vinyl group. Phenolic compound are well known for their antioxidant and radical scavenging properties [20][21][22][23] due to the resonance in the aromatic ring and the formation of quinone stabilizing the overall structure ( Fig. 3).…”
Section: Functionalization Through Acid Groupmentioning
confidence: 99%
“…It has been demonstrated that metal salts and metal ions, such as certain NPs with reactive sites on their surfaces, can induce oxidative stress through generation of ROS 90 - 94 . On the other hand, some nanoparticle coatings, such as derivatives of thiols or citric acids, are well-known hydroxyl radical scavengers 95 , 96 which can contribute to maintain an optimum physiological level of ROS in the cells. Moreover, the NPs may interact directly with the incoming ionizing radiation or any of the intermediate chemical products to alter the final spectrum and yield of ROS.…”
Section: Production Of Reactive Oxygen Speciesmentioning
confidence: 99%